Ensuring face support and control in soft ground urban tunnels: FEM validation. Issue 3 (3rd June 2022) - Konstantis, Spyridon; Prountzopoulos, George; Spyridis, Panagiotis
Abstract: When designing and constructing a tunnel in an urban setting with the use of a closed face Tunnel Boring Machine (TBM), the objective is to ensure both the tunnel face stability and the control of induced ground deformations within predefined, acceptable limits. Unless the exerted active face pressure will match the in situ ground stresses, there will be ground deformations taking place in the advance core, i.e., face extrusion and pre‐convergence, resulting in settlements or heave for active pressure lower or higher than the in situ stresses, respectively. This article presents the validation through finite element method (FEM) of an analytical methodology that can be applied on soft ground urban tunnels to assess the level of active face support to be considered in numerical analysis, to ensure elastic relaxation in the advance core and thus effective ground deformation control. The methodology combines the classic Anagnostou and Kovari method with the Convergence–Confinement method for face support proposed by Aristaghes and Autuori. In the current article, the methodology is described in detail and subsequently validated through three‐dimensional FEM analyses. The article concludes with a discussion on the results and the applicability range of the methodology.